Narrativas surdas: experiências na comunidade e na cultura surda e a constituição de identidades - Santos, Taiane Santos dos (2012)
This dissertation has as its aims narratives about experiences in the deaf community and deaf culture. It has been inspirited on narratives that focus on the spaces captured the experiences of deaf people and the processes of formation of their identities. It focus on discussing how a specific community of deaf people are forming their identities through the experiences of life in the deaf community. The subjects were five deaf people, that through previously scheduled meetings were encouraged to tell and share their stories lived in the deaf community. There were three meetings, two in small groups ( two and three people) and the last with all members of the research. With the narrative stories it was possible to identify common but singular identities, each formed from the experiences and perceptions of the world individually. The research is in a space of socialization of memories and experiences recorded in the meetings and narratives elicited very rich in details about the constitution of identities .These processes have taken place often in the midst of conflicts and new conceptions about the importance of sign language, deaf culture, deaf community, deaf movement the association of the deaf, deaf identities , family and the deaf considered a reference for other deaf people . These categories of analysis that have emerged as brands that have strengthened the constitution of identities of research subjects. The aim with this research deconstruct historically constructed narratives that linked the deaf disability, presenting narratives through the eyes of a specific group on their stories of struggle and resistance, which help to understand the constitution of cultural identities.